Local versus intravenous injections of skeletal muscle precursor cells in nonhuman primates with acute or chronic intrinsic urinary sphincter deficiency. Issue 1 (December 2016) - Williams, J.; Badlani, Gopal; Dean, Ashley; Lankford, Shannon; Poppante, Kimberly; Criswell, Tracy; Andersson, Karl-Erik
Abstract Background Many factors may influence the efficacy of cell therapy for intrinsic urinary sphincter deficiency (ISD), including the route of administration of the cells and the condition of the sphincter. The goal of this study was to compare local versus intravenous administration of autologous skeletal muscle precursor cells (skMPCs) when administered to nonhuman primates (NHPs) with either acute or chronic ISD. Methods Thirty-two adult female monkeys were divided into eight groups (n = 4/group): (1) control; (2) surgically induced ISD/no treatment; (3) acute ISD (6-week duration)/local vehicle only; (4) acute ISD/local skMPC injection; (5) acute ISD/systemic skMPC; (6) chronic ISD (6-month duration)/local vehicle; (7) chronic ISD/local skMPC; (8) chronic ISD/systemic skMPC. Maximal urethral pressures (MUP) were measured prior to ISD, prior to treatment and at 3 and 6 months following treatment. Quantitative histology was used to measure muscle/collagen content, somatic innervation, and vascularity of the sphincter complexes. Results In NHPs with acute ISD both systemic and local administration of skMPCs increased resting MUP values and sphincter muscle content (p  < 0.05 vs. ISD/vehicle). However, the effects of systemic skMPC administration were significantly lower than those of local injection (p  > 0.05). In NHPs with chronic ISD local skMPC administration had reduced (compared to NHPs with acute ISD) effects on MUP and sphincter muscle values (p  < 0.05 vs. acute ISD/skMPC); systemic administration had no effect. Pudendal nerve-stimulated increases in MUP were significant only in acute ISD NHPs with local skMPC treatment (p  < 0.05 vs. resting MUP). The extent of sphincter vascularization and innervation were directly related to MUP and sphincter muscle content. Conclusions Both the chronicity of ISD and the route of cell injection influence the efficacy of cell therapy in monkey models of ISD. This may be related to the relative ability of cells to stimulate vascularization and re-innervation in these different treatment conditions.